An intranasal stringent response vaccine targeting dendritic cells as a novel adjunctive therapy against tuberculosis - Karanika, Styliani; Gordy, James T.; Neupane, Pranita; Karantanos, Theodoros; Ruelas Castillo, Jennie; Quijada, Darla; Comstock, Kaitlyn; Sandhu, Avinaash K.; Kapoor, Aakanksha R.; Hui, Yinan; Ayeh, Samuel K.; Tasneen, Rokeya; et al. (Frontiers in Immunology, 2022)
Lengthy tuberculosis (TB) treatment is required to overcome the ability of a subpopulation of persistent Mycobacterium tuberculosis (Mtb) to remain in a non-replicating, antibiotic-tolerant state characterized by metabolic remodeling, including induction of the RelMtb-mediated stringent response. We developed a novel therapeutic DNA vaccine containing a fusion of the relMtb gene with the gene encoding the immature dendritic cell-targeting chemokine, MIP-3α/CCL20. To augment mucosal immune responses, intranasal delivery was also evaluated. We found that intramuscular delivery of the MIP-3α/relMtb (fusion) vaccine or intranasal delivery of the relMtb (non-fusion) vaccine potentiate isoniazid activity more than intramuscular delivery of the DNA vaccine expressing relMtb alone in a chronic TB mouse model (absolute reduction of Mtb burden: 0.63 log10 and 0.5 log10 colony-forming units, respectively; P=0.0002 and P=0.0052), inducing pronounced Mtb-protective immune signatures. The combined approach involving intranasal delivery of the DNA MIP-3α/relMtb fusion vaccine demonstrated the greatest mycobactericidal activity together with isoniazid when compared to each approach alone (absolute reduction of Mtb burden: 1.13 log10, when compared to the intramuscular vaccine targeting relMtb alone; P<0.0001), as well as robust systemic and local Th1 and Th17 responses. This DNA vaccination strategy may be a promising adjunctive approach combined with standard therapy to shorten curative TB treatment, and also serves as proof of concept for treating other chronic bacterial infections.